2021
DOI: 10.3892/etm.2021.10069
|View full text |Cite
|
Sign up to set email alerts
|

Secreted frizzled‑related protein 4 promotes brown adipocyte differentiation

Abstract: Secreted frizzled-related protein 4 (SFRP4) is a member of the SFRP family that contains a cysteine-rich domain homologous to the putative Wnt-binding site of frizzled proteins. In the present report, the effects of SFRP4 on murine brown adipocyte differentiation were evaluated, which exhibited an intrinsic capacity to differentiate with high efficiency. Brown preadipocytes were isolated from the scapular region of brown adipose tissue, which showed that the overexpression of recombinant active SFRP4 protein a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Secretory frizzled-related protein (SFRP) 4 is an extracellular antagonist of Wnt signalling and regulates adipogenesis [ 39 ]. Overexpression of recombinant active SFRP4 protein promotes brown adipocyte differentiation and induces CEBPα, UCP-1, PRDM16, PGC1α and GLUT4 expression in a dose-dependent manner [ 40 ]. However, SFRP4 is differentially expressed in the subcutaneous and visceral adipogenic differentiation of C57BL/6 mice and may play different roles [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Secretory frizzled-related protein (SFRP) 4 is an extracellular antagonist of Wnt signalling and regulates adipogenesis [ 39 ]. Overexpression of recombinant active SFRP4 protein promotes brown adipocyte differentiation and induces CEBPα, UCP-1, PRDM16, PGC1α and GLUT4 expression in a dose-dependent manner [ 40 ]. However, SFRP4 is differentially expressed in the subcutaneous and visceral adipogenic differentiation of C57BL/6 mice and may play different roles [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…qRT-PCRwas performed as previously described [ 14 , 20 ]. Briefly, total RNA was isolated from the aortas of the ApoE KO mice by using the TRIzol Plus (Invitrogen, Carlsbad, CA, USA), and a SuperScript® III First-Strand Synthesis System (Invitrogen, Carlsbad, CA, USA) was utilized to synthesize cDNA.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, it can also bind with the FZ receptor and afect the direction of intracellular signal transduction [7]. As a member of the SFRPs family, since the discovery of SFRP4 [10], studies on its role in diabetes [11], obesity [12], and lipid metabolism [13][14][15][16] have continuously revealed its important roles, providing a new direction and strategy for the treatment of diabetes and lipid metabolism-related diseases. In addition, the latest research studies found that SFRP4 also plays an important role in the occurrence and development of cardiovascular diseases [17].…”
Section: Introductionmentioning
confidence: 99%
“…Brown preadipocytes were isolated from the interscapular BAT of C57BL/6J mice aged 3 weeks using collagenase I digestion (Fig. 1B) [28]. The isolated cells were seeded in 6-well plates (1 × 10 6 cells/mL) and were cultured in Dulbecco's modified Eagle's medium (DMEM)/F12 medium containing 1% penicillin/streptomycin and 10% fetal bovine serum.…”
Section: Isolation and Culture Of Brown Preadipocytesmentioning
confidence: 99%